PEMANFAATAN APLIKASI iSUMBAR MAMBACO PADA PEMBELAJARAN JARAK JAUH SELAMA COVID-19 DI SDN 51 SUNGAI JARIANG - Indah Putri Rahman; Zulfahmi Hasibuan; Rendy Nugraha Frasandy (Journal Cerdas Mahasiswa, 2022)
The iSumbar Mambaco application is used as a distance learning process during Covid-19 at SDN 51 Sungai Jariang. Its use is considered very helpful and makes it easier for students to read books besides having to come to the school library, so that it becomes an attraction for researchers to study how to use the iSumbar Mambaco Application for Distance Learning (PJJ) during Covid-19 at SDN 51 Sungai Jariang. The aim of this research is to describe the use of the iSumbar Mambaco application for distance learning (PJJ) during Covid-19 at SDN 51 Sungai Jariang. The research method used is qualitative research. The research technique used is observation, interviews and documentation. Sources of data consisted of principals, deputy principals, homeroom educators, librarian and students at SDN 51 Sungai Jariang. The results of this study reveal findings about the Utilization of the iSumbar Mambaco Application in Distance Learning (PJJ) during Covid-19 at SDN 51 Sungai Jariang by inviting students to download the iSumbar Mambaco application, writing down the title of the book needed in the search section, and educators providing appropriate direction and learning. Involves the use of the iSumbar Mambaco Application. In the use of the iSumbar Mambaco application, it was found that the lack of parental participation in directing and guiding children to study at home during distance learning, the condition of the internet network, and the lack of tendency of students to read using the iSumbar Mambaco application. To overcome this, it is necessary to establish good cooperation between educators and parents of students, the importance of family effectiveness, and the school in using the iSumbar Mambaco application for distance learning.